Does pronounceability modulate the letter string deficit of children with dyslexia? A study with the rate and amount model - Marinelli, Chiara V.; Traficante, Daniela; Zoccolotti, Pierluigi (Frontiers in Psychology, 2014)
The locus of the deficit of children with dyslexia in dealing with strings of letters may be a deficit at a pre-lexical graphemic level or an inability to bind orthographic and phonological information. We evaluate these alternative hypotheses in two experiments by examining the role of stimulus pronounceability in a lexical decision task (LDT) and in a forced-choice letter discrimination task (Reicher–Wheeler paradigm). Seventeen fourth grade children with dyslexia and 24 peer control readers participated to two experiments. In the LDT children were presented with high-, low-frequency words, pronounceable pseudowords (such as DASU) and unpronounceable non-words (such as RNGM) of 4-, 5-, or 6- letters. No sign of group by pronounceability interaction was found when over-additivity was taken into account. Children with dyslexia were impaired when they had to process strings, not only of pronounceable stimuli but also of unpronounceable stimuli, a deficit well accounted for by a single global factor. Complementary results were obtained with the Reicher–Wheeler paradigm: both groups of children gained in accuracy in letter discrimination in the context of pronounceable primes (words and pseudowords) compared to unpronounceable primes (non-words). No global factor was detected in this task which requires the discrimination between a target letter and a competitor but does not involve simultaneous letter string processing. Overall, children with dyslexia show a selective difficulty in simultaneously processing a letter string as a whole, independent of its pronounceability; however, when the task involves isolated letter processing, also these children can make use of the ortho-phono-tactic information derived from a previously seen letter string. This pattern of findings is in keeping with the idea that an impairment in pre-lexical graphemic analysis may be a core deficit in developmental dyslexia.